Resurrecturis - musical triptych in the form of a concert requiem, composed by P. Ramovš, J. Trošt, and S. Vremšak - Barbo, Matjaž (Muzikološki zbornik, 2014)
The triptych of works written by P. Ramovš, J. Trošt, and S. Vremšak was conceived in the form of a concert requiem and dedicated to the memory of victims of the communist massacres after the WW II. The emphasised religious frame of a requiem is integrated into a secular aesthetic context, to be played in a concert hall before a concert audience.
Keywords: 20.st.; glasbeni triptihi; Ramovš, Primož, 1921-; rekviemi; slovenska glasba; Trošt, Jože, 1940-; Vremšak, Samo, 1930-